PROFIT SHARING MECHANISM IN PRULINK SYARIAH INVESTOR ACCOUNT PRODUCT IN THE PERSPECTIVE OF MUDHARABAH MUSYTARAKAH CONTRACT - Eva Mufdalifa (JURISTA: Jurnal Hukum dan Keadilan, 2017)
PRUlink Syariah Investor Account is one of the products launched by PT Prudential Insurance, which is a sharia insurance product with a single contribution combined between investment and insurance protection. PRUlink syari'ah is here to provide choices for the community in preparing for the future of his life and family. PRUlink syari'ah gives participants the option to choose what type of investment they want with each risk they have. Profit sharing of investment results is developed with a mudharabah musytarakah system. The insurance participants are the owners of capital (shahibul mal) and the sharia insurance company functions as a trustee (mudharib). The profit obtained from the development and it is divided between the participants and the company in accordance with the agreed provisions. This study aims to determine whether the application of mudharabah musytarakah at PT Prudential Insurance Sigli branch is in accordance with the principles contained in Islamic shariah. The results of this study are the application of the mudharabah musytarakah contract at PT Prudential Insurance Sigli branch is in accordance with the principles contained in Islamic shari'ah, the profits obtained will be put into the participant's pool of funds and then deducted by insurance costs. If there is an excess of funds remaining, it will be divided according to the principles of mudharabah musytarakah contract 70% of the profit for participants and 30% for the company. Profit sharing that is not in accordance with Islamic sharia principles is void.